Comparison of Price regarding the Domesticly Produced Medicine with the Price of the Similar Generic Medicine in India - Mohammad Hosein Motevalli; Amirreza Dowlati Beirami; Alireza Salimi; Nazila Yousefi (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat, 2022)
Background: Supporting domestic production, by assuming its effect on the increase of accessibility, has been acknowledged as one of the main pharmaceutical policies from two dimensions of better provision of the drugs in the market and the increase of affordability by reducing prices. Therefore, it is expected from the domestic industries to produce pharmaceutical products that, in addition to increasing access and a sustainable supply of drugs, have competitive prices compared to the rival imported products, and reduce the medical costs imposed on patients and the health system. In this study the price of domestically produced drugs were compared with the price of the similar generic ones in India. Methods: In this study, first, India was selected for comparison due to reasons such as low price, good quality, and the possibility of commerce despite sanctions. Then, from the Iranian pharmaceutical statistics, drugs which were only produced in Iran and were highly consumed with respect to the number of sales were included in the study. Prices of Iranian and Indian medicines were extracted from related valid websites. Finally, the price of 110 drugs were compared to determine the success rate of the domestic production industry in offering a reasonable price in the absence of foreign competitors. Results: According to the findings from 57 % of the drugs under study, the median consumer price of these drugs in India was lower than the Iranian consumer price. If this comparison was made with the minimum price of the Indian medicine, this percentage would reach 88. Conclusion: According to the findings mentioned above, it can be concluded that reducing the drugs prices and costs does not occur in all cases of domestic production, and this alone cannot be a good justification for a complete support of the domestic production of drugs; however, it should be noted that reducing costs is not the only reason to support domestic production of these products, and policy makers may act with regard to other factors in line with supportive policies; thus,  the reasons regarding each case should be clearly defined for the health system.